Women’s Welfare, Stunting, and Access to Reproductive Rights: An Overview of the Situation in Indonesia - Litaay, Simona Christina Henderika; Batjo, Sitti Nurjana (Universitas Pattimura, 2024)
This article explores the interconnection between women’s welfare, stunting, and access to reproductive rights in Indonesia, highlighting the often-overlooked role of women’s health and empowerment in combating child stunting. The study aims to analyze how structural barriers, gender inequality, and unmet reproductive health rights contribute to the persistence of stunting, particularly among children under five. Utilizing a literature review method, this research draws from scholarly databases and bibliometric analysis to examine relevant publications on stunting, women’s rights, gender, and reproductive health. The findings reveal that many healthcare services in Indonesia remain inadequate in fulfilling women’s reproductive rights, with limited access to essential services reflecting broader issues of gender injustice and state neglect. The novelty of this article lies in its integrated perspective that frames stunting not only as a child health issue but also as a gender and social equity concern. This study contributes to the social sciences and humanities by emphasizing the need for a holistic, long-term strategy that centers women as both rights holders and key agents in public health. It recommends policy reforms focused on reproductive justice, structural health equity, and the transformation of social norms to ensure that stunting prevention efforts are sustainable and gender-responsive.